PERAN KEPALA MADRASAH DALAM MENINGKATKAN PROFESIONALISME GURU DI MI AL-ISLAMIYAH KOTA BANGIL - Yulianti Yulianti; Anwar Sa’dullah; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
The Madrasah Head is an education leader at the education unit level who must have a strong leadership foundation. For this reason, every Madrasah head must understand the key to his leadership success. The success of the quality of education in Madrasah is largely determined by the level of success of Madrasah heads in managing and developing educators who are the foundation elements of the components available in Madrasas, the Madrasah head as an influential person in Madrasas and influential in developteacher professional competence. The Madrasah Head must assess the professional level of each individual teacher in teaching, so that he knows which needs to be maintained and which ones need to be increased in his professionalism.For this reason, the head of the Madrasah directs the guidance in which there is a good communication between the headmaster and each teacher. The Madrasah Head is also someone who is fully responsible for organizing educational activities, madrasa administration, fostering other education personnel, and empowering and choosing the facilities and infrastructure.  Keyword P: Head Of Madrasah,Teacher Professionalism